Geometrical effects on the surface plasmonic resonance by highly ordered Au nanostructures. (March 2019) - Park, Seongkyu; Song, Hyerin; Yoo, Dayoung; Kim, Kyujung; Kim, Yangdo; Lee, Dongyun
Abstract: Three differently shaped and highly ordered Au nanostructures were fabricated using an anodized aluminum oxide template and a thermal evaporator. A long-range ordered cone shape, embossed shape structure, and wave-like shape were obtained. Nanoparticles were added to the substrates with the three different shapes of ordered Au nanostructures, to verify the surface-enhanced Raman scattering by nanostructures with various shapes and gaps between structures. The simulation results showed the dependency of the Raman signal on the shape of the nanostructures, and hot-spots were found to depend largely on the distance between the structures and the wavelength of the incident light source. Thus, nanostructures can be designed to achieve various purposes by varying their shapes and the fabrication process. Graphical abstract: Highlights: Three differently shaped and highly ordered Au nanostructures were fabricated for understanding geometrical effect on SPR. Nanoparticles were added onto the Au nanostructures to verify geometrical effects with various nanostructures. The results exhibited dependency of the Raman signal on the shape of the nanostructures but no stereotypes exist. Nanostructures need to be designed to achieve various purposes by varying their shape and the process of their fabrication.